Predictors of shared decision-making among treatment-seeking emerging adults in primary care and community addiction and mental health settings: A cross-sectional study - Tyler Marshall; Karin Olson; Adam Abba-Aji; Xin-Min Li; Richard Lewanczuk; Sunita Vohra (PLoS ONE, 2025)
Background Shared decision-making (SDM) is a process in which healthcare providers (HCPs) and patients make health-related decisions collaboratively, guided by the best available evidence. Previous research suggests that emerging adults (aged 18–29) with mental health concerns might prefer SDM over traditional approaches; however, it remains unclear whether prevalent symptoms of anxiety, depression, or health-related quality of life (HRQL) are associated with the level of SDM that occurs during a clinical encounter. Objective This study explored whether prevalent symptoms of anxiety, depression or HRQL among emerging adults were associated with the perceived level of SDM involvement during a single clinic visit at a primary care or community addiction and mental health (AMH) setting. Methods A cross-sectional survey was conducted using a subset of data (emerging adults and their HCPs) obtained from an overarching study on SDM in adults (18–64 years) in Alberta, Canada. Sociodemographic data were collected and reported descriptively. SDM was the primary outcome variable and was measured dyadically (i.e., the mean score between HCPs and patients) using the Alberta Shared Decision-Making Instrument (ASK-MI). Symptoms of patient anxiety/depression and HRQL were measured using the Hospital Anxiety and Depression Scale (HADS) and the EQ-5D-5L. Pearson R correlation matrices were conducted to explore relationships between SDM, anxiety/depression, HRQL, and demographic variables. Results Forty-two emerging adult patients and 31 HCP dyads were recruited from six community AMH settings and eight primary care settings. The mean SDM dyad rating was 8.69 (SD, ± 2.01), indicating an “excellent” level of SDM. Symptoms of anxiety, depression, and HRQL were not significantly correlated with SDM dyad ratings during the clinic visit. Post hoc analyses showed that patient age was inversely related to SDM dyad ratings; R = −0.34, p = 0.03. Discussion In this study, emerging adults reported high levels of perceived engagement in SDM, regardless of their HRQL or symptoms of anxiety and depression. However, several limitations, such as the risk of performance bias, should be considered when interpreting these findings. To strengthen the evidence base, future research should aim to address these limitations.